Secondary hyperparathyroidism associated with papillary thyroid cancer - Neirotti, Rubens; Viana, Sherbourne; Lyford-Pike, Patrick; Otatti, Gabriela; Nin, Marcelo (Cirugía del Uruguay, 2005)
Association between primary hyperparathyroidism and differentiated thyroid cancer is we/1 known; there is, however, little evidence of relationship between this cancer and secondary hyperparathyroidism. In Surgical Clinic «F» Clinical Hospital - Faculty of Medicine - Montevideo, Uruguay, during the period ranging from January 2000 through June 2002, twenty-two patients suffering from secondary hyperparathyroidism were subject to surgery. One of the patients operated, presented association with papillary thyroid cancer. lt is the first case to be found in our country and Nr. 23 in the international literature we consulted.